Soil-Structure Interaction Effect on Fragility Curve of 3D Models of Concrete Moment-Resisting Buildings - Ali Anvarsamarin; Fayaz Rahimzadeh Rofooei; Masoud Nekooei (Shock and Vibration)
This paper presents the probabilistic generation of collapse fragility curves for evaluating the performance of 3D, reinforced concrete (RC) moment-resisting building models, considering soil-structure interaction (SSI) by concentration on seismic uncertainties. It considers collapse as the loss of lateral load-resisting capacity of the building structures due to severe ground shaking and consequent large interstory drifts intensified by P-Δ effects as well as the strength and stiffness deterioration of their lateral load carrying systems. The estimation of the collapse performance of structures requires the relation between the intensity measure (IM) and the probability of collapse that is determined using the generated collapse fragility curves. Considering a number of 6-, 12-, and 18-story, 3D, RC moment-resisting buildings, two scalar IMs are employed to estimate their collapse fragility curve. On the other hand, the effect of the site soil type on the collapse fragility curves was taken into account by considering the soil-structure interaction. According to the obtained results, adopting the average of spectral acceleration (Saavg) intensity measure is more efficient in capturing the effect of the inherent uncertainties of the strong ground motions on the structural response parameters. In addition, considering the SSI for soil type D with shear-wave velocity of 180 m/s to 360 m/s reduces the median of intensity measure (IM = Sa(T1)) of fragility curve in 6-, 12-, and 18-story buildings by 4.92%, 22.26%, and 23.03%, respectively.